Об одном алгоритме повышения достоверности выяления событий в системе автоматического констроля и слежения за нераспространением радиоктивних материалов - Буртняк, В.М. (Моделювання та інформаційні технології, 2010)
Is examined the algorithm of events exposure authenticity increase at control and looking for objects with radio-active materials. The resulted algorithm of this task decision does possible the decline of appearance of «false» event to the set probability.